PERAMALAN TINGKAT KEMISKINAN DI KOTA MEDAN DENGAN METODE MOVING AVERAGE (MA) PERIODE 2017-2026 - Asyifa Maesa Putri, Dania; Suci Amanda, Silvyana; Nabila, Najwa; Dwie Astika , Shavira (Jurnal Multidisiplin Sosial dan Humaniora, 2024)
This study aims to forecast the poverty rate in Medan City using the Moving Average (MA) method for the period 2017-2026. Historical data on poverty rates from 2017 to 2022 are used as the basis for forecasting. The Moving Average method is chosen due to its simplicity in smoothing data and identifying trends. The results of this study are expected to provide an overview of future poverty trends and serve as a reference for policymakers in designing poverty reduction strategies.